DEVELOPMENT OF MICROTEACHING LEARNING MODEL BASED ON EXPERIENTIAL LEARNING THROUGH ROLE OF MODELS AND GROUPS - Yudi Supiyanto; Heny Sulistyaningrum; Henny Sri Astuty (FKIP ULM, 2021)
One learning model that prioritizes direct experience is experiential learning. Experiential learning orientates learning to direct experience. This follows the objectives of microteaching courses. The purposes of the study were: 1. Developing a microteaching learning model based on experiential learning through models and groups to improve qualified teaching skills/practical and effective, 2. Developing supporting the administration of microteaching learning model based on experiential learning through the role of models and groups to improve qualified teaching skills /practical, and effective. This research used a developmental study using Plomp model, which consisted of five stages. Furthermore, to assess the quality of microteaching learning models based on experiential learning, Nieveen criteria was used to fulfil the practicality and effectiveness. The study results were based on the practical aspects of management, lecturer and student activities on learning using microteaching learning models based on experiential learning through the role of models and groups with an overall average of 3.5 with very good indicators. It had very practical implementation. The result of the effectiveness data analysis from student learning outcomes, lecturer response questionnaire, and student response questionnaire to microteaching learning, had good average learning outcomes. The effectiveness data analysis from student learning outcomes, lecturer response questionnaire, and student response questionnaire to microteaching learning model based on experiential learning through the role of models and groups had good average learning outcomes.Keywords: Experiential Learning; Micro Teaching; Teaching Skills